Mercury isotopes as tracers of ecology and metabolism in two sympatric shark species. (October 2020) - Le Croizier, Gaël; Lorrain, Anne; Sonke, Jeroen E.; Jaquemet, Sébastien; Schaal, Gauthier; Renedo, Marina; Besnard, Lucien; Cherel, Yves; Point, David
Abstract: In coastal ecosystems, top predators are exposed to a wide variety of nutrient and contaminant sources due to the diversity of trophic webs within inshore marine habitats. Mercury contamination could represent an additional threat to shark populations that are declining worldwide. Here we measured total mercury, carbon and nitrogen isotopes, as well as mercury isotopes, in two co-occurring shark species (the bull shark Carcharhinus leucas and the tiger shark Galeocerdo cuvier ) and their potential prey from a coastal ecosystem of the western Indian Ocean (La Réunion Island). Our primary goals were to (i) determine the main trophic Hg sources for sharks and (ii) better characterize their diet composition and foraging habitat. Hg isotope signatures (Δ 199 Hg and δ 202 Hg) of shark prey suggested that bull sharks were exposed to methylmercury (MeHg) produced in offshore epipelagic waters, while tiger sharks were exposed to offshore mesopelagic MeHg with additional microbial transformation in slope sediments. Δ 199 Hg values efficiently traced the ecology of the two predators, demonstrating that bull sharks targeted coastal prey in shallow waters while tiger sharks were mainly foraging on mesopelagic species in the deeper waters of the island slope. Unexpectedly, we found a positive shift in δ 202 Hg (>1‰) between sharks and their prey, leading to high δ 202 Hg values in the two shark species (e.g. 1.91 ± 0.52‰ in bull sharks). This large shift in δ 202 Hg indicates that sharks may display strong MeHg demethylation abilities, possibly reflecting evolutionary pathways for mitigating their MeHg contamination. Graphical abstract: Image 1 Highlights: Mercury isotopes were analyzed in bull and tiger sharks from the Indian Ocean. Hg MIF signature revealed that bull sharks target coastal prey in shallow water. Δ 199 Hg values showed that tiger sharks forage in deeper habitat on the island slope. δ 202 Hg shift between prey and predators may indicate MeHg demethylation in sharks.